Comparative statistical analysis new urban road pavement versus conventional pavement of pervious concrete - de Oliveira, Evailton Arantes (2019)
This research proposes a variation to pervious concrete pavement, in which a mixture of cement, aggregates and water includes calcium hydroxide additive (Ca(OH)2). This new approach focuses on two main environmental functions: increased permeability of urban soil favoring a decrease of total and peak runoff and resulting reduction of flood occurrence in the cities, and CO2 absorption from the atmosphere, contributing to reduction of the negative impacts caused by the observed increased greenhouse effect in the cities. A series of 40 conventional pervious concrete pavement samples and 30 specimens of the proposed urban pavement were tested in the laboratory for permeability, density, porosity and compression resistance, and monitored for CO2 absorption. Results show that there is an environmental benefit of CO2 sequestration when adding Ca(OH)2 to pervious concrete, but there is also a decrease in its compressive strength and permeability.